Sectoral income - Geir B. Asheim; Taoyuan Wei (University of Oslo, Department of Economics, 2007)
What is the income of each sector of an economy? E.g., in the case of a country endowed with petroleum resources, what is the income of its petroleum sector? Here we present a definition of sectoral income, which is compatible with an important line of theoretical literature on comprehensive national accounting. We do so first by splitting national income into individual income and then defining sectoral income by considering the contributions to individual income that the sectors give rise to.
Keywords: C43; D60; O47; 330; Sectoral income; comprehensive national accounting; Volkseinkommen; Branchenentwicklung; Theorie